Development of an Authentic Self-Assessment Instrument to Measure Employability Skills and Science Literacy of High School Students in North Aceh - Agus Muliaman; Halimatus Sakdiah; Fajrul Wahdi Ginting; Najiha Sabirin; Zahara (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The independent curriculum implemented at the elementary to higher education level currently hopes to produce a superior generation. Employability Skills and Scientific Literacy are two things must be possessed by superior human resources. In order to measure these two abilities, an appropriate instrument is needed, such as authentic self-assessment. This study aims to develop an authentic self-assessment to measure the Employability Skills and Scientific Literacy of high school students. This research is a development research using 4D design (Define, Design, Develop, and Disseminate). The instruments used were validity and response questionnaires filled in by expert lecturers and senior teachers at the school. The results of this study are: a) the authentic self-assessment instrument measures Employability Skills - the average is in the high category and the response is very good and b) the authentic self-assessment instrument measures students' scientific literacy - the average is in the high category and the response is very good.